Penyebab dan Resiko Stunting: Implikasi Terhadap Pendidikan Anak Usia Dini - Syefriani Darnis (Lembaga Sosial Rumah Indonesia, 2022)
Stunting is caused by multidimensional factors and not only caused by malnutrition experienced by pregnant women and children under five years. This research is library research. The results of the study stated that the stunting problem occurs starting from the womb and will be seen when the child reaches the age of two years, some of the effects of stunting can be seen, among others, impaired child height and weight growth, child growth and development is not optimal, does not have a good effect. on children's intelligence and learning abilities, and children are susceptible to disease. The most decisive intervention to reduce the prevalence of stunting, therefore, needs to be carried out in the first 1,000 days of a toddler's life, including good nutrition for pregnant women which of course is also needed by the baby in the womb, healthy food intake and nutrition as a complementary food for breast milk for children - children (make sure children get good nutrition, especially during pregnancy until the age of 1000 children), maintain a clean environment and most importantly provide awareness to parents, especially mothers to have the knowledge and apply good parenting for children.